CRISPR-Cas9 Gene Editing for Sickle Cell Disease and β-Thalassemia. Issue 6 (June 2021) - Frangoul, Haydar; Altshuler, David; Cappellini, M. Domenica; Chen, Yi-Shan; Domm, Jennifer; Eustace, Brenda K.; Foell, Juergen; de la Fuente, Josu; Grupp, Stephan; Handgretinger, Rupert; Ho, Tony W.; Kattamis, Antonis; et al.
Abstract : (Abstracted from N Engl J Med 2021;384:252–260) Transfusion-dependent β-thalassemia (TDT) and sickle cell disease (SCD) are the most common inherited hematologic disorders, affecting approximately 60, 000 and 300, 000 patients worldwide, respectively. Current therapies, including red blood cell (RBC) transfusion and iron chelation in TDT and transfusion, pain management, and hydroxyurea in SCD, help to manage the disorders but do not address the underlying cause.